X-3+X+((X-3)*3)=38

Simple and best practice solution for X-3+X+((X-3)*3)=38 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X-3+X+((X-3)*3)=38 equation:


Simplifying
X + -3 + X + ((X + -3) * 3) = 38

Reorder the terms:
X + -3 + X + ((-3 + X) * 3) = 38

Reorder the terms for easier multiplication:
X + -3 + X + (3(-3 + X)) = 38
X + -3 + X + ((-3 * 3 + X * 3)) = 38
X + -3 + X + ((-9 + 3X)) = 38
X + -3 + X + (-9 + 3X) = 38

Remove parenthesis around (-9 + 3X)
X + -3 + X + -9 + 3X = 38

Reorder the terms:
-3 + -9 + X + X + 3X = 38

Combine like terms: -3 + -9 = -12
-12 + X + X + 3X = 38

Combine like terms: X + X = 2X
-12 + 2X + 3X = 38

Combine like terms: 2X + 3X = 5X
-12 + 5X = 38

Solving
-12 + 5X = 38

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '12' to each side of the equation.
-12 + 12 + 5X = 38 + 12

Combine like terms: -12 + 12 = 0
0 + 5X = 38 + 12
5X = 38 + 12

Combine like terms: 38 + 12 = 50
5X = 50

Divide each side by '5'.
X = 10

Simplifying
X = 10

See similar equations:

| (49/7)+3=100/50 | | y=(1/2)x-18 | | -5.1x+4.1=6.7x-1.8 | | 3(-6x)= | | 4x-4/8-3=5 | | Z^2(2z-1)=0 | | 13-7x=94-28x | | (49/7)+3=100/10 | | 5q+11=26 | | (49/7)+3=100/3 | | 50t+6=-7 | | 5t-a=8t | | (49/7)+3=100/7 | | (49/7)+3=100/ | | 5(x+9)-2x=18 | | 2y=-7+3 | | 7y+9=4y | | 4(6)+3y=18 | | lnx=-7 | | X^4=8x^2+20 | | 16x+1+25=122 | | b(13b+5)=8 | | x+4-6=2x-6 | | 16x+26=122 | | 8x=9x-5/2 | | x^2=6x+4 | | 3.67+3= | | -4x^2+24x=0 | | (X-3)+x+((x-3)*3)=38 | | 9b-2=-38 | | 15n-4=41 | | 7n+2=9 |

Equations solver categories